The deep blue sea for beginners a novel - Rice, Luanne (Bantam Books, 2009)
Years ago, Lyra Davis left behind a world of wealth and privilege and the people she loved most in the world, unable to reconcile the expectations of her celebrated family with the longings of her own wild heart. Now she lives quietly among a community of expatriates on the isle of Capri--until her daughter Pell travels across an ocean to find the mother she remembers and the deeper truths they all need so desperately.